PENGARUH KOMBINASI PUPUK ORGANIK TERHADAP PRODUKSI TERUNG (Solanum melongena L) SEBAGAI SUMBER BELAJAR BIOLOGI SMA - Sutiani, Ni Wayan; Oka, Anak Agung (UNIVERSITAS MUHAMMADIYAH METRO, 2013)
Learning process is most emphasized for how student learn to a concept which can we get from environment. Teacher can exploiting research product as media and source learn to student toÂ be understands concept easier. Data which got to analize passÂ from Analysis Variation (ANAVA) is obtained from Fhit 15,98 > Fdaf 2,35 in real level 0,05, so that Fhit > Fdaf, so refuse H0 dan H1Â accepted. While from test âBeda Nyata Jujurâ obtained treat B gives best influent for eggplant production, because diferencce between treat B by traet A, C, and D is biggest than BNJ value. From this analysis has cocluded there is influence organic fertilizer for eggplant plant, and withÂ combination organic (pen 50%:compost 50%) gives best influent for eggplant production. BenefitÂ from research product as resource Biologi program for Senior High School is to supports interest competence based on KTSP and hoped student can apply their comprehension about growth and blooming concept in everyday life, so, in learning activity is most emphasized to skill process.Kata Kunci: kombinasi pupuk organik, produksi terung.